Three decades of wetland transformation in the middle and lower Yangtze River Basin: classification, inundation dynamics, and ecological impacts - Pingheng Li; Qing Wang; Muhammad Umair; Nargizakhon Shamshieva; Yichen Zheng (Ecological Indicators)
Wetlands in the Upper Mekong River Basin (UMRB) have experienced profound structural and hydrological transformations over the past two decades, driven by intensified land use and upstream hydrological engineering. This study investigates wetland classification and inundation dynamics across the UMRB from 2002 to 2022, employing a multi-tiered remote sensing framework that integrates morphological features, topographic context, seasonal flooding patterns, and landscape configuration using time-series Landsat data. Six wetland categories were mapped with high thematic accuracy, revealing a net wetland area decline of 2,763.5 km2, primarily due to agricultural encroachment and hydropower expansion. Notably, natural wetlands such as floodplain marshes and riparian forests contracted by 1,188.4 km2, while artificial reservoirs and aquaculture zones expanded substantially. Cluster analysis of inundation frequency time series identified four dominant hydrological patterns, with 52.6 % of natural wetland pixels exhibiting a persistent drying trend and shortened flood duration. These hydrological shifts were closely linked to regional dam operations, altered monsoon patterns, and land reclamation pressures. The results underscore the limitations of area-based wetland metrics in rapidly developing transboundary basins and highlight the need for dynamic, function-oriented monitoring approaches. By coupling spatiotemporal classification with inundation trend clustering, this study offers a transferable framework for assessing ecological degradation and supporting evidence-based wetland management under intensifying climate and anthropogenic stressors.